Brief report: Cyberbullying perpetration and its associations with socio‐demographics, aggressive behaviour at school, and mental health outcomes. Issue 8 (25th October 2014) - Fletcher, Adam; Fitzgerald‐Yau, Natasha; Jones, Rebecca; Allen, Elizabeth; Viner, Russell M.; Bonell, Chris
ABSTRACT: Relatively little is known about those who cyberbully others, especially in a UK context. We drew on data from 1144 young people aged 12–13 in eight English secondary schools to examine the prevalence of cyberbullying perpetration and its associations with socio‐demographics, other behaviours, and health outcomes. Overall, 14.1% of respondents reported ever cyberbullying others with no significant differences by gender or socio‐economic status. Drawing on mixed‐effects logistic regression models, first we found a strong, dose–response relationship between aggressive behaviour at school and cyberbullying others, suggesting that cyberbullying may not only be a facet of wider patterns of bullying but also of aggression more broadly. Second, cyberbullying others was associated with poorer quality of life and with psychological difficulties but not with peer/social problems or worse mental wellbeing. Longitudinal studies are needed to assess whether such associations are causal. Highlights: There is a strong, dose–response relationship between aggressive behaviours at school and cyberbullying others. Cyberbullying may not only be a facet of wider patterns of bullying but also of aggressive behaviours more broadly. Cyberbullies reported more hyperactivity and conduct problems but not more peer problems or worse mental wellbeing.